Sociālo mediju ietekmētāju kā mārketinga instrumenta loma patērētāju pirkšanas uzvedības veidošanā Indijas mazumtirdzniecības sektorā - Singh, Swapanjit (Latvijas Universitāte, 2025)
The study examines the role of social media influencers in shaping consumer purchasing behaviour within India’s retail sector, focusing on how influencers impact consumer trust, engagement, and decision-making. In today’s digital landscape, social media has become a vital marketing channel, enabling brands to connect with consumers on a personal level through influencers who often embody relatable and authentic personas. This study aims to assess the effectiveness of influencer marketing by analysing key factors such as influencer credibility, authenticity, and alignment with consumer values. Additionally, it evaluates how industry-specific strategies, like the "Vocal for Local" initiative, resonate with Indian consumers and impact their purchasing behaviour. Using a quantitative research methodology, data was gathered from a representative sample of social media users in India, primarily within the 18-44 age range, through an online survey. The survey captured respondents' attitudes, trust levels, and purchasing intentions influenced by social media influencers, specifically in the fashion, beauty, lifestyle, and electronics sectors. Findings reveal that younger consumers (18-34 years), who are highly engaged on social media, form the primary audience for influencer marketing campaigns. The study highlights that 70% of respondents exhibit a stronger likelihood to make a purchase if they share values with an influencer, underscoring the critical role of value alignment in influencer marketing. Additionally, 84% of respondents prioritize transparency and honesty, indicating that influencer credibility is essential for fostering consumer trust. The study further identifies that income plays a role in influencing purchasing decisions, as middle-income consumers (earning between $500 and $1000) show significant interest in influencer recommendations but remain price sensitive. Trust in influencer endorsements directly affects willingness to pay a premium, with 45% of respondents open to spending more on products endorsed by trusted influencers. However, skepticism towards influencer marketing persists, as 32% of respondents express distrust, reflecting the need for careful influencer selection and transparent disclosure practices. The research synthesizes these findings with existing literature, reaffirming that influencer marketing is a powerful tool for engaging consumers and enhancing brand credibility, but also highlights challenges associated with universal trust in influencer endorsements. The study recommends that brands prioritize authentic influencers who align with consumer values and utilize data analytics to optimize influencer selection. Additionally, integrating transparency and leveraging social commerce tools can enhance consumer experience and improve conversion rates. These insights underscore the potential of influencer marketing as an effective strategy within India’s evolving retail landscape, where authenticity, consumer-aligned messaging, and strategic influencer partnerships are key to driving engagement and loyalty.
The Role of Social Media Influencers as a Marketing Tool in Shaping Consumer Purchasing Behaviour in the Indian Retail Sector
Keywords: Ekonomika un uzņēmējdarbība